Comprehensive Assessmentof Comfort (Motion Sickness) in Vehicles. - Vega Quezada, Mateo Nicolas (My University, 2024)
Abstract This study investigates technologies to assess and mitigate motion sickness in vehicles. It aims to evaluate existing technologies for the detection and mitigation of motion sickness in vehicles, analyze their effectiveness, and explore practical applications and improvements for future vehicle systems. The research is divided into two sections: the first is a practical approach given by a literature review of patents related to motion sickness detection and mitigation, followed by a real-world implementation of an experiment based on the findings. The second part evaluates the improvement of the ISO 2631-1 standard for assessing motion sickness, using computational tools. The literature review identified 23 relevant patents from an initial pool, focusing on technologies and methods related to vehicle dynamics, human physiology, and interactions with the vehicle or passenger. The experimental section involved 14 participants subjected to three different scenarios: anticipatory cues (vibrotactile and auditory) and a control group. Results showed a significant reduction in motion sickness with anticipatory cues compared to the control. The study also compares the performance of a lower-degree filter with the ISO-provided filter using the Motion Sickness Dose Value (MSDV) metric, demonstrating that lowergrade filters can perform similarly with minimal differences. The findings highlight the need for a more refined research focus and deeper technological analysis, suggesting improvements in patent categorization, experiment design, and consultation with subject matter experts.
Keywords: Keywords: Motion sickness, Passenger, Comfort, Patent, Detection, Mitigation, Anticipatory- Cues, MSDV, Filter.